The Territorial Dimension Of Politics : Within, Among, And Across Nations - Duchacek, Ivo D., 1913-1988 (Routledge, 2019)
This comparative study examines the dialectical tensions between global and regional interdependence and the fragmentation of humankind into territorial entities. Political authority may remain territory-bound, but borders increasingly are penetrated by pollutants, individuals, noncentral governments in search of foreign trade and investment, and transnational corporations, as well as the traditional exchanges of trade, media, and culture. The result of these transborder flows, accelerated by new technologies, is a new variety of international relations among "perforated sovereignties.â€ Dr. Duchacek analyzes the territorial organization of political authority in both democratic and authoritarian frameworks as well as in unitary and federal systems. Case studies focus on new forms of transborder interactions between neighboring countries, especially in North America and in Western Europe. The book is of major interest to scholars in the fields of political science and political economy. Quotations from a variety of political theorists and practitioners, illustrative diagrams, and maps make the book suitable for students of comparative politics, international relations, comparative federalism, and public policy